Digital Democracy and the Challenges of Freedom of Expression in Indonesia - Jhames Jorgi; Hery Firmansyah (Jurnal Ilmu Hukum Kyadiren, 2026)
The rapid development of social media has significantly expanded opportunities for public participation and freedom of expression. However, it has also generated various legal challenges, including defamation, hate speech, the dissemination of misinformation, and the potential criminalization of public criticism. This study aims to examine the legal framework governing freedom of expression on social media within the Indonesian legal system, identify the legal issues arising from the exercise of freedom of expression in digital spaces, and formulate the legal boundaries of such freedom based on the principles of the rule of law, democracy, and human rights. This research employs a normative juridical method using statutory, conceptual, and human rights approaches through the analysis of primary, secondary, and tertiary legal materials. The findings indicate that freedom of expression is constitutionally protected under the 1945 Constitution of the Republic of Indonesia, the Human Rights Law, and various international human rights instruments. Nevertheless, its exercise is subject to limitations intended to safeguard the rights, freedoms, and legitimate interests of others. The study concludes that proportional law enforcement, enhanced legal certainty, and improved digital literacy are essential to maintaining an appropriate balance between freedom of expression and the protection of public interests in the digital sphere.